Optimal Monetary Policy in the Presence of Pricing-to-Market - Jochen Michaelis (Universität Kassel, Fachbereich Wirtschaftswissenschaften, 2005)
This paper presents a general-equilibrium framework to revisit the issues of optimal monetary policies and international policy coordination in a two-country model, focusing on the role of a pricing-to-market (PTM) policy by firms. Both countries may be different with respect to PTM. Using the set-up developed by Corsetti and Pesenti (2001a) and Betts and Devereux (2000a,b), we show that (i) for a given Foreign monetary stance, a Home monetary expansion is beneficial for both countries only if Home PTM is at an intermediate range; (ii) in a world Nash equilibrium Home and Foreign welfare are bell-shaped in the degrees of PTM; (iii) relative welfare crucially depends on the degrees of PTM; (iv) there is a welfare gain from cooperation even in the cases of no and full PTM.
Keywords: E40; F42; F41; 330; pricing to market; terms of trade; international coordination of monetary policies; Geldpolitik; Internationale wirtschaftspolitische Koordination; Allgemeines Gleichgewicht; Zwei-Länder-Modell; Exchange rate pass-through; Terms of Trade; Nash-Gleichgewicht; Wohlfahrtseffekt; beggar-thy-neighbour